DOI: 10.21007/etd.cghs.2009.0296
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Potential of Reassortant Swine Influenza A Viruses

Abstract: DEDICATIONThis dissertation is dedicated to my husband, Jason Staats, who has been my rock through the hardest years of this process, and to my parents Beth and Bill Brockwell, who have supported and encouraged me always.iv ACKNOWLEDGEMENTS I would like to thank my advisor, Dr. Richard Webby, for giving me the opportunity to work in his lab and for the excellent training I have received. I would also like to thank my

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 142 publications
(219 reference statements)
0
5
0
Order By: Relevance
“…In previous coinfection experiments with the classical swine virus, no reassortants were detected. 66 However, we see that MN/99 is capable of reassorting with TX/96 and produces a greater variety of viral genotypes than NC/02 and TX/96. When genotyping 96 potential reassortant viruses, we identified 34 different reassortant viruses between MN/99 and TX/96 compared to only 19 reassortant genotypes between NC/02 and TX/96.…”
Section: In Vitro Reassortmentmentioning
confidence: 78%
See 4 more Smart Citations
“…In previous coinfection experiments with the classical swine virus, no reassortants were detected. 66 However, we see that MN/99 is capable of reassorting with TX/96 and produces a greater variety of viral genotypes than NC/02 and TX/96. When genotyping 96 potential reassortant viruses, we identified 34 different reassortant viruses between MN/99 and TX/96 compared to only 19 reassortant genotypes between NC/02 and TX/96.…”
Section: In Vitro Reassortmentmentioning
confidence: 78%
“…This followed the pattern of lower titers and poor transmission when swine have been experimentally infected as has been previously reported and based on what has been seen epidemiologically. 66 More extensive evaluation of the swine, human, and 6+2 viruses in the pSRECs revealed that there is little difference in growth abilities (Figure 3-6). The only significant difference observed was that TX/96 had a higher titer than MN/99 at 20 hpi (P<0.05).…”
Section: Psrec Growth Kineticsmentioning
confidence: 97%
See 3 more Smart Citations